Reimagining Conscientization: A Model to Map, Track, and Expand Popular Education Praxis - Kamil M. Gerónimo-López; Roberto Thomas; Luis Calderón Reyes (Adult Education Research Conference, 2025)
This paper introduces the Conscientization Wheel, a participatory model grounded in popular education, aimed at facilitating conscientization through four interconnected dimensions: raising awareness, empathizing and building solidarity, thinking critically, and nurturing a love for the world, applicable in various learning contexts.
Keywords: Popular education; conscientization; adult education; liberatory models; praxis